Validation of the SCEC Broadband Platform simulations for tall building risk assessments considering spectral shape and duration of the ground motion. (11th July 2018) - Bijelić, Nenad; Lin, Ting; Deierlein, Greg G.
Summary: Earthquake simulation technologies are advancing to the stage of enabling realistic simulations of past earthquakes as well as characterizations of more extreme events, thus holding promise of yielding novel insights and data for earthquake engineering. With the goal of developing confidence in the engineering applications of simulated ground motions, this paper focuses on validation of simulations for response history analysis through comparative assessments of building performance obtained using sets of recorded and simulated motions. Simulated ground motions of past earthquakes, obtained through a larger validation study of the Southern California Earthquake Center Broadband Platform, are used for the case study. Two tall buildings, a 20‐story concrete frame and a 42‐story concrete core wall building, are analyzed under comparable sets of simulated and recorded motions at increasing levels of ground motion intensity, up to structural collapse, to check for statistically significant differences between the responses to simulated and recorded motions. Spectral shape and significant duration are explicitly considered when selecting ground motions. Considered demands include story drift ratios, floor accelerations, and collapse response. These comparisons not only yield similar results in most cases but also reveal instances where certain simulated ground motions can result in biased responses. The source of bias is traced to differences in correlations of spectral values in some of the stochastic ground motion simulations. When the differences in correlations are removed, simulated and recorded motions yield comparable results. This study highlights the utility of physics‐based simulations, and particularly the Southern California Earthquake Center Broadband Platform as a useful tool for engineering applications.